Muons as a tool for background rejection in imaging atmospheric Cherenkov telescope arrays - Olivera-Nieto, L.; Mitchell, A. M. W.; Bernloehr, K.; Hinton, J. A. (European Physical Journal C: Particles and Fields, 2021)
The presence of muons in air-showers initiated by cosmic ray protons and nuclei is well established as a powerful tool to separate such showers from those initiated by gamma rays. However, so far this approach has been fully exploited only for ground level particle detecting arrays. We explore the feasibility of using Cherenkov light from muons as a background rejection tool for imaging atmospheric Cherenkov telescope arrays at the highest energies. We adopt an analytical model of the Cherenkov light from individual muons to allow rapid simulation of a large number of showers in a hybrid mode. This allows us to explore the very high background rejection power regime at acceptable cost in terms of computing time. We show that for very large (≳ 20 m mirror diameter) telescopes, efficient identification of muon light can potentially lead to background rejection levels up to 10- 5 whilst retaining high efficiency for gamma rays. While many challenges remain in the effective exploitation of the muon Cherenkov light in the data analysis for imaging Cherenkov telescope arrays, our study indicates that for arrays containing at least one large telescope, this is a very worthwhile endeavor.
CRIS-Team Scopus Importer:2021-12-24